Whole Genome or Single Genes? A Phylodynamic and Bibliometric Analysis of PRRSV - Frias-De-Diego, Alba; Jara, Manuel; Pecoraro, Brittany M.; Crisci, Elisa (Frontiers in Veterinary Science, 2021)
Diversity, ecology, and evolution of viruses are commonly determined through phylogenetics, an accurate tool for the identification and study of lineages with different pathological characteristics within the same species. In the case of PRRSV, evolutionary research has divided into two main branches based on the use of a specific gene (i.e. ORF5) or whole genome sequences as the input used to produce the phylogeny. In this study, we performed a review on PRRSV phylogenetic literature and characterized the spatiotemporal trends in research of single gene versus whole genome evolutionary approaches. Finally, using publicly available data, we produced a Bayesian phylodynamic analysis following each research branch and compared the results to determine the pros and cons of each particular approach. This study provides an exploration of the two main phylogenetic research lines applied for PRRSV evolution, as well as an example of the differences found when both methods are applied to the same database. We expect that our results will serve as a guidance for future PRRSV phylogenetic research.